Conformational Diversity in Contryphans from Conus Venom: cis–trans Isomerisation and Aromatic/Proline Interactions in the 23‐Membered Ring of a 7‐Residue Peptide Disulfide Loop. Issue 45 (23rd September 2013) - Sonti, Rajesh; Gowd, Konkallu Hanumae; Rao, K. N. Shashanka; Ragothama, Srinivasarao; Rodriguez, Alex; Perez, Juan Jesus; Balaram, Padmanabhan
Abstract Conformational diversity or "shapeshifting" in cyclic peptide natural products can, in principle, confer a single molecular entity with the property of binding to multiple receptors. Conformational equilibria have been probed in the contryphans, which are peptides derived from Conus venom possessing a 23‐membered cyclic disulfide moiety. The natural sequences derived from Conus inscriptus, GCVDLYPWC* (In936) and Conus loroisii, GCPDWDPWC* (Lo959) differ in the number of proline residues within the macrocyclic ring. Structural characterisation of distinct conformational states arising from cis–trans equilibria about Xxx–Pro bonds is reported. Isomerisation about the C2–P3 bond is observed in the case of Lo959 and about the Y5–P6 bond in In936. Evidence is presented for as many as four distinct species in the case of the synthetic analogue V3P In936. The Tyr‐Pro‐Trp segment in In936 is characterised by distinct sidechain orientations as a consequence of aromatic/proline interactions as evidenced by specific sidechain–sidechain nuclear Overhauser effects and ring current shifted proton chemical shifts. Molecular dynamics simulations suggest that Tyr5 and Trp7 sidechain conformations are correlated and depend on the geometry of the Xxx–Pro bond. Thermodynamic parameters are derived for the cis↔ trans equilibrium for In936. Studies on synthetic analogues provide insights into the role of sequence effects in modulating isomerisation about Xxx–Pro bonds.